The diet of yellow-vented bulbul (pycnonotus goiavier) in oil palm agroecosystems - Amit, B.; Andrew Alek, Tuen; Haron, Khalid; Harun, M.H.; Norman, Hj Kamarudin (Lembaga Minyak Sawit Malaysia, 2015)
The Yellow-vented Bulbul (Pycnonotus goiavier) is one of the most sighted birds in oil palm plantation. A study on their dietary habits was conducted at the Durafarm Oil Palm Plantation from February 2011 to May 2013 to determine the reason behind their abundance. In this study, 45 individuals of P. goiavier were dissected for stomach content analysis. Ivlev's electivity index (E) was used to measure the degree of food selection by P. goiavier. The results showed that this bird species mainly selected the Order Coleoptera (mostly pollinating weevil) (E= +0.97) and Homoptera (E= +0.87) as their main food sources in the oil palm plantation. This bird also selected Order Diptera (E= -0.30), Hemiptera (E= -0.43) and Hymenoptera (E= -0.92) as a prey based on their abundance. However, this species mainly avoided feeding on insects from Order Odonata, Orthoptera, Dictyoptera and Lepidoptera (E=-1.0 each) in oil palm plantation. There is a weak negative correlation found for the distribution of P. goiavier with the abundance of insects in oil palm plantation. Further investigation is needed on this bird species towards predating the oil palm pollinating weevil, since it could possibly affect the population density of the pollinating weevil and subsequently the oil palm fruit set.